Pengaruh Motivasi Dan Keyakinan Kemampuan Diri Terhadap Minat Berwirausaha Mahasiswa Jurusan Manajemen Fakultas Ekonomi Dan Bisnis Universitas Islam Malang - Meilinda Hamida Hasan; Nurhidayah Nurhidayah; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
Abstrak This study aims to determine the effect of motivation and self-efficacy beliefs on the entrepreneurial interest of student majoring ini management, Faculty of Economics anda Business, Islamic University of Malang. The population in this study were undergraduate students majoring in management, economics and business faculty in 2018. The sampling technique used was purposive sampling with the slovin formula targeted at 85 student majoring ini management. The place of research was conducted in the management department of the Faculty of Economics and Business, Islamic University of Malang. Teh data analysis method used classical assumption test and multiple linear regression to analyze teh data using the SPSS 14 application of windows evalution version. The results showed that motivation had a significant effect on interest in entrepreneurship. However, self-efficacy beliefs have ni significant effect on entrepreneurial interest. Keywords : Motivation, Self-Efficacy, Interest In Entrepreneurship